A Spatial Decision Support Tool for Alternate Conservation and Impact Assessment - A Case Study - Kaur, Ravinder; Srivastava, Rajesh; Betne, Rajeev; Mishra, Kamal; Dutta, D. (Journal of Soil and Water Conservation, 2022)
A Spatial Decision Support System (SDSS) for estimating sediment yields under prevailing resource management systems as well as for proposing and assessing impacts of alternate conservation practice plans on soil loss from a watershed was developed. Validation of the proposed SDSS on 9-year sediment yield data for Nagwan watershed in Damodar-Barakar catchment in India revealed that it could quite realistically mimic the annual dynamics of the total sediment yields at the test watershed outlet with a correlation coefficient of 0.65; model efficiency coefficient of 0.70; mean relative error of —17.97% and root mean square prediction error of 9.63 t/ha. Both linear programming (LP) and simple watershed prioritization criteria bases alternate conservation practice plans were designed for the test watershed. Incorporation of these conservation plans into the proposed SDSS showed that LP based optimized conservation plan, covering 72% of total watershed area, could lead to a maximum reduction (44.16%) in the total soil loss from the watershed. This was followed by the three prioritization criteria based conservation practice plans on 51, 29 and 22% of the test watershed area which lead to about 27.74, 12.05 and 15.15% reduction, respectively in the total soil loss from the watershed. However, Benefit: Cost analysis of these conservation practice plans revealed that the LP based conservation plan (on 72% of total watershed area) was not as economically feasible as implanting conservation practices on just 22% of the total watershed area